Continuous Trastuzumab Therapy in Breast Cancer Patients With Asymptomatic Left Ventricular Dysfunction. (3rd August 2015) - Yu, Anthony F.; Yadav, Nandini U.; Eaton, Anne A.; Lung, Betty Y.; Thaler, Howard T.; Liu, Jennifer E.; Hudis, Clifford A.; Dang, Chau T.; Steingart, Richard M.
Abstract : Background: Adjuvant trastuzumab is a highly effective targeted treatment that improves survival for patients with HER2‐positive breast cancer. However, trastuzumab interruption is recommended for patients who develop treatment‐induced cardiotoxicity (i.e., decline in left ventricular ejection fraction [LVEF], with or without symptoms) and can lead to an incomplete course of treatment. We studied the cardiac safety of continuous trastuzumab therapy among patients with asymptomatic declines in LVEF. Methods: We retrospectively evaluated patients with HER2‐positive breast cancer treated with adjuvant trastuzumab at our institution between 2005 and 2010. Treatment‐induced cardiotoxicity was defined by an absolute decrease in LVEF of ≥10% to below 55% or an absolute decrease of ≥16%. Logistic regression was used to determine the association between candidate risk factors and treatment‐induced cardiotoxicity. Results: Among 573 patients, 92 (16%) developed treatment‐induced cardiotoxicity. Trastuzumab was continued without interruption in 31 of 92 patients with treatment‐induced cardiotoxicity—all were asymptomatic with LVEF of ≥50% at cardiotoxicity diagnosis with median LVEF of 53% (range, 50%–63%), and none developed heart failure during follow‐up. Risk factors associated with treatment‐induced cardiotoxicity included age ( p = .011), anthracycline chemotherapy ( p = .002), and lower pretrastuzumab LVEF ( p < .001). Conclusion: Among patients who develop asymptomatic treatment‐induced cardiotoxicity with LVEF of ≥50%, continuous trastuzumab therapy appears to be safe. Implications for Practice: Cardiotoxicity is the most common reason for patients with HER2‐positive breast cancer to receive an incomplete course of life‐saving trastuzumab therapy. Data from this study suggest that continuous trastuzumab may be safe in patients with asymptomatic cardiotoxicity and left ventricular ejection fraction of ≥50%. Given the substantial oncologic benefit of trastuzumab, increasing efforts are needed to ensure that patients complete the full course of treatment without interruption. Current recommendations for trastuzumab interruption in patients who develop cardiotoxicity should be re‐evaluated. Abstract : This study evaluated patients with HER2‐positive breast cancer treated with adjuvant trastuzumab at Memorial Sloan Kettering Cancer Center between 2005 and 2010. Logistic regression was used to determine the association between candidate risk factors and treatment‐induced cardiotoxicity. Among patients who develop asymptomatic treatment‐induced cardiotoxicity with left ventricular ejection fraction of ≥50%, continuous trastuzumab therapy appears to be safe.